KNOWLEDGE AND ATTITUDES OF BRIDES-TO-BE RELATED TO STUNTING PREVENTION: PENGETAHUAN DAN SIKAP CALON PENGANTIN TERKAIT PENCEGAHAN STUNTING - Ayawaila, Adrian Paskalis; Rahmawati, Apriana; Lubis, Erika; Pamungkas, Indra Gilang (Politeknik Kesehatan Kemenkes RI Jakarta I, 2025)
Stunting is a condition of failure to grow due to chronic malnutrition from pregnancy to the age of five, which has an impact on the physical and cognitive development of children. The incidence of stunting in Indonesia ranges from 27.22% to 28.11%. This shows that more than a quarter of the population is stunted. This prevention should be done far before pregnancy. This study was conducted to analyse the relationship between knowledge and stunting prevention attitudes in brides-to-be in Pondok Melati District, Bekasi City. The method used in this study is cross-sectional. Data was collected through a questionnaire filled out by 150 brides-to-be using total sampling. Bivariate analysis was performed using the chi-square test. The results found that there was a significant relationship between the knowledge and attitude of the bride-to-be regarding stunting prevention with a p-value of 0.000 (p-value < 0.05). These results emphasize the importance of education about stunting for brides-to-be, especially related to nutrition before and during pregnancy and the long-term impact of stunting on children.